2023
DOI: 10.3390/jof9030301
|View full text |Cite
|
Sign up to set email alerts
|

Assembling Quality Genomes of Flax Fungal Pathogens from Oxford Nanopore Technologies Data

Abstract: Flax (Linum usitatissimum L.) is attacked by numerous devastating fungal pathogens, including Colletotrichum lini, Aureobasidium pullulans, and Fusarium verticillioides (Fusarium moniliforme). The effective control of flax diseases follows the paradigm of extensive molecular research on pathogenicity. However, such studies require quality genome sequences of the studied organisms. This article reports on the approaches to assembling a high-quality fungal genome from the Oxford Nanopore Technologies data. We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 78 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…While the usage of medaka for diploid cells has been controversial because of the diploid nature of yeast, we found that the newer version of medaka provided more accurate assemblies. These results are in line with Sigova et al [ 32 ]. In their study, they reported that read correction with medaka is superior to read correction with racon in fungal pathogens.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…While the usage of medaka for diploid cells has been controversial because of the diploid nature of yeast, we found that the newer version of medaka provided more accurate assemblies. These results are in line with Sigova et al [ 32 ]. In their study, they reported that read correction with medaka is superior to read correction with racon in fungal pathogens.…”
Section: Resultssupporting
confidence: 94%
“…In their study, they reported that read correction with medaka is superior to read correction with racon in fungal pathogens. In addition, the percentage of genome completeness significantly decreases (by ~40%) when a reference is added, even after using six read correction tools [ 32 ]. Moreover, Zhang et al showed that medaka performance was superior against other read correction/polishing tools in which medaka improved the continuity and reduced mismatches in S. cerevisiae -assembled genomes [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the read correction tools, medaka was also more superior than flye and racon in genome completeness in all four species samples (Figure 1). These results are in line with Sigova et al [32]. In their study, they reported that read correction with medaka is superior to read correction with racon in fungal pathogens.…”
Section: Resultssupporting
confidence: 90%
“…In their study, they reported that read correction with medaka is superior to read correction with racon in fungal pathogens. In addition, the percentage of genome completeness significantly decreases (by ~40%) when a reference is added, even after using six read correction tools [32]. Genome completeness is majorly affected by sequencing methods and genome assembly tools rather than read correction tools [33].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, DNA sequences that are frequently used for phylogenetic studies have been obtained for 203 flax fungal pathogens including various Fusarium spp. [17,[96][97][98], Colletotrichum lini [99], Aureobasidium pullulans [99], Septoria linicola [23] and Melampsora lini [100,101]. These sequences can be used to develop PCR-based detection systems for flax pathogen identification [13] and are of great use for studying the virulence mechanisms of these pathogens and improving management strategies.…”
Section: Pathogen Characterizationmentioning
confidence: 99%